Kreativitas Gerak Pada Ekstrakurikuler Seni Tari Bertema Kehidupan Peduli Lingkungan di Kelas IV dan V SDN 80 Lemeu Pit Kabupaten Lebong - Puja Rapita; Dwi Anggraini; Lukman Lukman (Universitas Bengkulu, 2022)
The aim of the study was to describe motion creativity in extracurricular dance art themed environmental care life in fourth and fifth grades SDN 80 Lemeu Pit Lebong District. It applied of qualitative method used taxonomic approach. The respondents were the fourth and the fifth grade students who followed extracurriculer dance art at SDN 80 Lemeu Pit Lebong District. The instruments of the researched were interview giudelines and observation guidelines. The data were collected by interviewed, observation, and documentation during the process of extracurricular dance art. The data analysis technique using the spradley model, was taxonomic analysis. The data validition test were increased persistence, triangulation, and membercheck. The result of the research showed that the process of creativity in created motion in extracurricular dance art arised through the exploration, improvisation, evaluation, and formation phase. Conclusion of the research was the students could be creatived in created dance motion themed environmental care life.